Child maltreatment and neglect in the United Arab Emirates and relationship with low self-esteem and symptoms of depression. (3rd April 2021) - Shah, Syed M.; Nowshad, Gul; Dhaheri, Fatima Al; Al-Shamsi, Mariam H.; Al-Ketbi, Alfan M.; Galadari, Alaa; Joshi, Priyam; Bendak, Heba; Grivna, Michal; Arnone, Danilo
Abstract: Objectives: To our knowledge, this study is the first in the United Arab Emirates (UAE) to investigate the prevalence of child maltreatment in relation to depressive symptoms and self-esteem. Study design: Exposure to physical maltreatment, emotional abuse and neglect was evaluated in 518 adolescents (86% response rate) randomly selected from schools in Al Ain in the Emirate of Abu Dhabi. The Rosenberg self-esteem scale and the Beck Depression Inventory were used to measure self-esteem and depressive symptoms by using multivariate logistic regression analyses. Results: The mean age of study participants was 14.3 years. Emotional abuse was the most frequent form of maltreatment (33.9%), physical abuse (12.6%) and neglect (12.1%) followed. Male sex was a positive predictor of physical abuse (OR = 2.12; 95% CI 1.18–3.77), whilst higher maternal level of education was protective (OR = 0.40; 95% CI 0.19–0.86). Daily screen time (OR = 2.77; 95% CI 1.17–6.56) and tobacco smoking (OR = 1.86; 95% CI 1.09–3.18) positively predicted emotional abuse. Emotionally maltreated and neglected participants were less likely to report high level of self-esteem and more likely to report symptoms of depression. Conclusions: Child maltreatment in the UAE is of a similar magnitude to what reported in other countries around the world and significantly associated with low self-esteem and depressive symptoms.